Hubungan Faktor Perilaku Dengan Kunjungan Lansia Di Posbindu Lansia - Astriani Astriani; Muhammad Syafar; Rahmawati Azis (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: the elderly are healthy adults who undergo a process of change into weak and vulnerable people due to the lack of most of the physiological system reserves and increased susceptibility to various diseases and death. Objective: To determine factors related to elderly visits at posbindu for the elderly. Method; This type of research is quantitative with an analytical survey, using a cross-sectional approach. The sample in this study was 60 elderly people. Sampling in this study used a non-random sampling method using the Total Sampling technique. Data collection through questionnaires and analyzed by univariate, bivariate, and multivariate. Results: The results showed that knowledge, attitudes, emotional support, and needs were significantly related to the utilization of posbindu for the elderly. Meanwhile, family support, care support, and information media in statistical tests were not related to the use of posbindu in the elderly. The emotional support of the elderly has the most influence on the use of posbindu for the elderly, with a significant value (sig.=0.003) or p<0.015 and Exp(B)=5.935. Conclusion: that the emotional support of the elderly towards the posyandu is the most influential factor in the utilization of the posyandu. All parties are expected to support and help each other, motivate and assist and assist the elderly to always take advantage of the posyandu for the elderly on a regular and continuous basis.